2019
DOI: 10.1101/684076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invariants of Frameshifted Variants

Abstract: Frameshifts in protein coding sequences are widely perceived as resulting in either non-functional or even deleterious protein products. Indeed, frameshifts typically lead to markedly altered protein sequences and premature stop codons. By analyzing complete proteomes from all three domains of life, we demonstrate that, in contrast, several key physicochemical properties of protein sequences exhibit significant robustness against +1 and −1 frameshifts in their mRNA coding sequences. In particular, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The origin of a new gene within an existing gene is termed ''overprinting'' (Keese and Gibbs, 1992). Advantageous for same-strand overlaps is that the hydrophobicity profile of a frame-shifted sequence tends to be similar to that of the unshifted sequence (Bartonek et al, 2020), as may have contributed to the origin of an OLG in SARS-CoV-2 (Nelson et al, 2020a). Intriguingly, overlaps of the reference frame ''+1'' and antisense ''À1'' tend to have opposite hydrophobicities for their amino acids (Konecny et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of a new gene within an existing gene is termed ''overprinting'' (Keese and Gibbs, 1992). Advantageous for same-strand overlaps is that the hydrophobicity profile of a frame-shifted sequence tends to be similar to that of the unshifted sequence (Bartonek et al, 2020), as may have contributed to the origin of an OLG in SARS-CoV-2 (Nelson et al, 2020a). Intriguingly, overlaps of the reference frame ''+1'' and antisense ''À1'' tend to have opposite hydrophobicities for their amino acids (Konecny et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when point mutations change the amino acid, the new amino acid coded for is likely to have similar biochemical properties due to the code's organization (17) . Monte Carlo simulations have shown that the extant genetic code is significantly more robust to substitution and frameshift mutations than randomly generated genetic codes (18)(19)(20)(21)(22) . Premature stop codons and frameshift errors can be introduced by substitutions or indels (insertions and deletions).…”
Section: Introductionmentioning
confidence: 99%